Contribution to Celastraceae palynology from Cerrado forest fragments: a focus on shape, amb and exine ornamentation - Torrati-Guioti, Paloma Gaspar (2023)
Forest fragments in the Cerrado are areas of prominent biological importance due to their great species richness and biodiversity. These areas host endemic species of Celastraceae, the knowledge of which contributes to the preservation of this biome. This study aims to characterize the pollen morphology of 10 native species of Celastraceae found in forest fragments in the state of São Paulo, Brazil, contributing to the knowledge of the taxa for future taxonomic studies, and providing data for the conservation of the species in the forest areas. The pollen grains were acetolyzed, measured, described qualitatively and illustrated using light microscopy and scanning electron microscopy. The pollen characters referring to the pollen unit, polarity, type and number of apertures are similar in all the species studied. The shape, amb and exine ornamentation of pollen grains are the diagnostic qualitative morphological data for Celastraceae in this study. Microreticulate pollen grains were observed in Celastrus, Hippocratea and Pristimera; reticulate pollen grains with a very thick exine characterize the analyzed species of Plenckia; and reticulate and microreticulate ornamentation was observed among the species of Monteverdia. The results obtained here allow us to distinguish species of the analyzed genera and confirm the pollen diversity previously reported for Celastraceae.